Investigating the Relationship between Anxiety of School-age Children Undergoing Surgery and Parental State-trait Anxiety - Fatemeh Heshmati Nabavi; Malihe Shoja; Monir Ramezani; Azadeh Saki; Marjan Joodi (Mashhad University of Medical Sciences, 2017)
Background: Surgery is a stressful experience for children, and preoperative anxiety in children could be affected by the level of parental anxiety. Aim: The aim of this study was to determine the relationship between anxiety in school-age children before surgery and parental state-trait anxiety. Method: This descriptive study was performed on 81 children within the age group of 6-12 years admitted for elective surgical operation and 128 parents in Doctor Sheikh Hospital, Mashhad, Iran, 2016. Children's anxiety and parental anxiety were measured before the entrance of the patients to the operating room via Revised Children's Manifest Anxiety Scale (RCMAS) and Spielberger's State-Trait Anxiety Inventory, respectively. The data was analyzed in SPSS, version 16, using the relevant statistical tests. Results: The results of Pearson product-moment correlation test showed a positive correlation between children's anxiety and fathers' state anxiety and between children's anxiety and mothers' state anxiety (r=0.27, r=0.41; P=0.005, P=0.040, respectively). However, no statistically significant relationship was observed between children's anxiety and parents' trait anxiety, age of children, as well as parents' educational level, occupation, and level of trait anxiety. Implications for Practice: Considering the association between parents' state anxiety and children's anxiety, implementing preoperative interventions to prepare parents for surgery is recommended.